High Power Figure‐of‐Merit, 10.6‐kV AlGaN/GaN Lateral Schottky Barrier Diode with Single Channel and Sub‐100‐µm Anode‐to‐Cathode Spacing. Issue 37 (22nd July 2022) - Xu, Ru; Chen, Peng; Zhou, Jing; Li, Yimeng; Li, Yuyin; Zhu, Tinggang; Cheng, Kai; Chen, Dunjun; Xie, Zili; Ye, Jiandong; Liu, Bin; Xiu, Xiangqian; et al.
Abstract: GaN‐based lateral Schottky barrier diodes (SBDs) have attracted great attention for high‐power applications due to its combined high electron mobility and large critical breakdown field. However, the breakdown voltage ( BV ) of the SBDs are far from exploiting the material advantages of GaN at present, limiting the desire to use GaN for ultra‐high voltage (UHV) applications. Then, a golden question is whether the excellent properties of GaN‐based materials can be practically used in the UHV field? Here, UHV AlGaN/GaN SBDs are demonstrated on sapphire with a BV of 10.6 kV, a specific on‐resistance ( R ON, SP ) of 25.8 mΩ cm 2, yielding a power figure‐of‐merit (P‐FOM =  BV 2 / R ON, SP ) of 4.35 GW cm −2 . These devices are designed with single channel and 85‐µm anode‐to‐cathode spacing, without other additional electric field management, demonstrating its great potential for the UHV application in power electronics. Abstract : The 10.6 kV ultral‐high voltage AlGaN/GaN lateral Schottky barrier diodes with single AlGaN/GaN channel and the cathode‐to‐anode spacing of 85 µm are demonstrated. Combining with a specific on‐resistance of 25.8 mΩ cm 2 of the device, the power figure of merit can be as high as 4.35 GW cm −2, which is the highest value reported so far.